Cash Waqf Linked Sukuk Financing in the Development of Sustainable Agriculture from the Maqashid Syari'ah Perspective - Ahsani Taqwiem; Kartika Rose Rachmadi (ITB AAS INDONESIA Surakarta, 2023)
The agricultural sector has a fairly large share in the country's development goals, but one of the main problems that always becomes an obstacle for farmers is capital support. The APBN that has been set by the government has not been able to be distributed evenly. Waqf is one of the Islamic social finances that has great potential, although until now its realization is still very minimal. This study tries to synergize waqf with integrated agricultural development in Brenjonk using a qualitative method with a case study approach. The results of this study offer a scheme that can help farmers to obtain financial assistance in agricultural development efforts through the Cash Waqf linked Sukuk instrument. CWLS yields can be allocated by BWI as Nazhir to Brenjonk organic farmers in the form of financing assistance for infrastructure development, skills training or procurement of tools that can facilitate the performance of farmers. Considering that waqf is a social fund, any assistance distributed to the target group is free of charge.